Why do Marshrutkas Exist in One City and Not in Others? Toward a Political Economy of Routes in Russian Urban Public Transportation - Muleev, Egor (Journal of Economic Sociology, 2020)
Urban public transportation in Russia has changed significantly since the fall of the USSR. In many cities, marshrutkas have completely replaced the classical public modes of transportation. Other cities have, however, tried to balance the electric transport system with marshrutkas. Some cities also have trams and articulated buses on their streets, with minibuses completely absent. The reasons for such huge differences are not obvious. Various approaches have failed to explain why marshrutkas are present on the streets in one city but absent in others. The hypothesis here is that the routes were privatized by marshrutka-operating companies. The conceptual framework is based on the works of Karl Polanyi, Vadim Volkov, and Michael Burawoy. Nineteen in-depth interviews were conducted in the autumn of 2016: eight in Moscow, one in St. Petersburg, and ten in provincial cities, such as Nizhny Novgorod, Kazan, Ulyanovsk, Dimitrovgrad, and Cherepovetz. Research has shown that the fundamental problem for marshrutka operators is the danger of the reconsideration of route owners’ property rights. The difference between cities with and cities without marshrutkas is described not only in terms of a continuance of property rights but also through spatial characteristics of the industrial backgrounds. This view on urban public transport calls for a fresh discussion on regulation issues in transportation studies, the commodification of mobility, and the political economy of transport.